Between parallels 20 and 30 - Analyzing and proposing public policies for museums in Southern Brazil (2012) (Cadernos de Sociomuseologia, 2014)
Because the social changes of contemporaneity, the organization of the brazilian museums in the present situation, demands modifications and it will suffer improvements if based on sociomuseology. The development of a national museologic policy is a task of established authorities and this thesis has as objective to analyze public policies to museums, understanding its operation and application. From an historical research about the museologic systematization in the states of Paraná and Rio Grande do Sul and from researches within museologic institutions we try to include the cultural managers‘ voices and other social actors involved. The nowadays museologic systemic model doesn‘t show itself, as sociologists determinate, in a pattern that operates in web, with changes between states‘ and national systems. Points to a correct application and evaluation of museums policies would solve a lot of questions that worry the museums nowadays, being an inclusive, participatory and democratic cultural policy. Keywords: museums, public agents, public policy, museology.